Research on Different Irrigation Water Effect on Soda Alkaline Soil and Horizontal Drainage Water Salinity-alkalinity - Y.H. Wang (Chemical Engineering Transactions, 2016)
The effect of tube-well water and river water irrigation on soda alkaline soil and horizontal drainage water salinity-alkalinity was studied. Through soil column simulated experiment, the influence of the tube-well water and river water irrigation on soda alkaline soil and horizontal drainage water salinity-alkalinity was studied. The salinity indexes of surface drainage water in puddling period, the rules of salt ions change of surface drainage water, and the soil electrical conductivity changes in prime field period and the change of soil salinity indexes after a growing season were analyzed. The results showed that, there was no significant different of irrigationwater on salinity-alkalinity index for the first surface drainage water in puddling period. But the EC, Na+,Ca2++Mg2+ and total alkalinity of CK 1 was significant higher than CK 2 for the second drainage water. Irrigation water quality has not significant influence on the soil EC, but desulfurization gypsum could significantly reduce EC value of 0 to 10 cm soil layer. After one rice growth period, the T1 with pH and EC value was significantly less than T2 in 20-40 cm soil layer, but there no significant different on the top layer. Therefore, the tube-well water was choosing at the puddling period, so as to increase the surface flushing effect. With the corresponding, the river water was choosing at the prime field period to prevent soil secondary salinization.